2015
DOI: 10.1111/chd.12294
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Financial Impact of Ordering an Echocardiogram in Children with Left Axis Deviation on Their Electrocardiogram

Abstract: In presence of LAD on ECG, the sensitivity, specificity, and positive and negative predictive values of PE by a pediatric cardiologist are excellent at identifying CHD. Performing an ECHO on patients with LAD on ECG is only cost effective in the presence of an abnormal PE. In the presence of normal PE, there is a possibility of missing incidental structural cardiac disease in approximately 2% if an ECHO is not performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…Four of the identified patients had partial atrioventricular canal defects, in which LAD is expected secondary to displacement of the A-V node posteriorly and His bundle inferiorly. 3 Although LAD has been described in patients with both primum and secundum ASDs 13 and congenitally corrected transposition of the great arteries, 14 it is not classically associated with the other defects that were appreciated in our study. LAD in these patients may reflect a normal, coincidental variant given that anatomically the conduction system should not be disrupted or displaced from the usual position.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Four of the identified patients had partial atrioventricular canal defects, in which LAD is expected secondary to displacement of the A-V node posteriorly and His bundle inferiorly. 3 Although LAD has been described in patients with both primum and secundum ASDs 13 and congenitally corrected transposition of the great arteries, 14 it is not classically associated with the other defects that were appreciated in our study. LAD in these patients may reflect a normal, coincidental variant given that anatomically the conduction system should not be disrupted or displaced from the usual position.…”
Section: Discussionmentioning
confidence: 56%
“…A previous study by Ravi et al 13 revealed that consultation with a pediatric cardiologist was the most cost-effective initial step in further evaluation of patients with LAD.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, our data show a rare rate of severe/urgent pathology for lower acuity locations, making a strategy of a thorough inpatient cardiology consultation for these indications (with a possible delay in diagnosis) likely safe from a patient care standpoint. Lastly, recent publications have also demonstrated low‐reliability of EKGs in identifying cardiac pathology as it pertains to left ventricular hypertrophy in vasovagal syncope patients, and left axis deviation in asymptomatic children, further supporting cardiology evaluation rather than direct echocardiogram ordering in those situations …”
Section: Discussionmentioning
confidence: 99%
“…12 In addition, previously discussed issues of decreased auscultatory skills of general pediatricians and trainees may also play a role in the low rate of pathology found in echocardiograms performed for murmur indications. 12,13 Our final aim was to evaluate the prevalence of cardiology consultation prior to performed echocardiograms in our tertiary academic child- 18,19 This study was retrospective and is susceptible to limitations inherent to such a study design. The study relied on accurate documentation especially as it pertained to cardiology consultation taking place prior to the echocardiogram being performed.…”
Section: -Severementioning
confidence: 99%